2010
DOI: 10.1016/j.rmed.2010.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal moderate to severe asthma on perinatal outcomes

Abstract: Mothers with severe and moderate asthma during pregnancy have a higher risk of SGA babies than those with mild asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 46 publications
4
39
0
Order By: Relevance
“…Asthma was defined as physician-diagnosed asthma (whether confirmed or subject self-reported), or an asthma diagnosis as coded in a database or asthma fulfilling American Thoracic Society criteria. Females with asthma were further classified by symptom severity according to national and international guidelines (Global Initiative for Asthma or National Asthma Education Program Working Group on Asthma and Pregnancy) [13], number of medications used to control asthma symptoms (one drug: mild; two and three drugs: moderate/severe) [21] or a validated index combining medication use and markers of exacerbation (table 1) [22,23]. Exacerbations of asthma were defined (table 2) as symptoms requiring medical interventions such as hospitalisation, emergency department visits, other unscheduled urgent visits to the doctor or the use of emergency treatment.…”
Section: Inclusion Criteriamentioning
confidence: 99%
See 3 more Smart Citations
“…Asthma was defined as physician-diagnosed asthma (whether confirmed or subject self-reported), or an asthma diagnosis as coded in a database or asthma fulfilling American Thoracic Society criteria. Females with asthma were further classified by symptom severity according to national and international guidelines (Global Initiative for Asthma or National Asthma Education Program Working Group on Asthma and Pregnancy) [13], number of medications used to control asthma symptoms (one drug: mild; two and three drugs: moderate/severe) [21] or a validated index combining medication use and markers of exacerbation (table 1) [22,23]. Exacerbations of asthma were defined (table 2) as symptoms requiring medical interventions such as hospitalisation, emergency department visits, other unscheduled urgent visits to the doctor or the use of emergency treatment.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Relationship between asthma severity and perinatal outcomes Pre-term delivery There were three studies reporting on the effect of maternal asthma severity on pre-term delivery [13,21,22]. One retrospective [21] and one prospective study [13] reported early pre-term delivery at ,32 weeks of completed gestation as an outcome.…”
Section: Small For Gestational Agementioning
confidence: 99%
See 2 more Smart Citations
“…Bronchial asthma complicating pregnancies were 4 in number. FaranakFiroozi 13 has found that lack of oxygen to the fetus can lead to hypoxia combined with respiratory alkalosis that decrease the placental blood flow. Decreased fetal blood oxygen could result in both an abnormal growth and abnormal fetal development causing perinatal mortality, low birth weight and prematurity and IUGR.…”
Section: Observations and Resultsmentioning
confidence: 99%